A “bioethical case” in modern Greece - Louis (Χρήστος Λούης), Christos (Bioethica, 2019)
I present here a medical case with serious bioethical implications that took place in Athens approximately 90 years ago. To verify whether a small epidemic of an unknown infectious disease on the island of Syros was due to Dengue fever or to leptospirosis, a physician working at the Hellenic Pasteur Institute injected serum/blood taken from three epidemic victims into three institutionalized psychiatric patients without their or their legal guardians’ consent. The results of this experiment led the physician to the conclusion that the epidemic was indeed due to Dengue fever. Although a short while later, after additional investigations, the Pasteur Institute in Paris came to the opposite conclusion the Ministry of Health insisted on the original diagnosis and took no measures against leptospirosis. Fortunately the epidemic on Syros, as well as discussions in medical circles ceased soon thereafter. There was no legal follow-up of the initial lawsuit against the physician for murder attempt, given that the only one of the injected individuals who got sick as a result of this had been cured, and suffered no long-term effects.